A single case study of family resilience after parental death - Tanacıoğlu, Betül. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2015., 2015)
The main purpose of this study was to explore the factors that help family members adapt to parental death. Since any type of loss affects relationships, roles, and life goals, it was important to provide the whole picture of a family via a family systems perspective through using various data sources. To gather in-depth data about a family, a single case study design of qualitative approach was employed. Through a purposeful convenience sampling method, a family that had experienced loss of the mother became the case for the current study. For screening, DSM-V “Persistent Complex Bereavement Disorder” criteria were used. Data was collected through demographic forms and semi-structured interviews. The data was transcribed and then analyzed by using a thematic analysis procedure. Six themes emerged from the data: life after the diagnosis, mediators of mourning, life after loss, family members’ future plans, school perspective and family resilience. Findings revealed that the fact that the mother’s death was due to an illness was a facilitating factor for the family because of the predictability of loss. Also, religious beliefs, open communication, social support and economic resources of the family were helpful in their overcoming their experience of loss. This study was important in the sense that it gave an in-depth perspective of a Muslim family who lost the maternal parent, which is considered a person’s most important attachment figure.
Keywords: Parents -- Death.; Parents -- Death -- Psychological aspects.